Captive and free-living urban pigeons (Columba livia) from Brazil as carriers of multidrug-resistant pathogenic Escherichia coli. (January 2017) - Borges, Clarissa A.; Maluta, Renato P.; Beraldo, Lívia G.; Cardozo, Marita V.; Guastalli, Elisabete A.L.; Kariyawasam, Subhashinie; DebRoy, Chitrita; Ávila, Fernando A.
Highlights: Free-living and captive pigeons in Brazil carry multidrug-resistant Escherichia coli and virulence-associated genes (VAGs). VAGs include those found in avian pathogenic E. coli (APEC) and human extra-intestinal pathogenic E. coli (ExPEC). The VAGs hlyF, tsh and sitA were present in some high and intermediate pathogenicity isolates of E. coli from pigeons. Serotypes and sequence types detected in E. coli from pigeons included types found in poultry with colibacillosis. Pigeons may act as reservoirs for pathogenic E. coli . Abstract: Thirty Escherichia coli isolates from captive and free-living pigeons in Brazil were characterised. Virulence-associated genes identified in pigeons included those which occur relatively frequently in avian pathogenic E. coli (APEC) from commercial poultry worldwide. Eleven of 30 E. coli isolates from pigeons, belonging mainly to B1 and B2 phylogenetic groups, had high or intermediate pathogenicity for 1-day-old chicks. The frequency of multi-drug resistant (MDR) E. coli in captive pigeons was relatively high and included one isolate positive for the extended-spectrum β-lactamase (ESBL) gene bla CTX-M-8 . Pulsed field gel electrophoresis (PFGE) showed high heterogeneity among isolates. There is potential for pigeons to transmit antibiotic resistant pathogenic E. coli to other species through environmental contamination or direct contact.